The Influence of Employer Branding and Compensation on Employee Retention with Job Satisfaction as a Mediating Variable (A Study at Klinik Utama Mata Rawat Jalan Kepanjen Eye Center) - Olivia Carolina Angga Setyorini, Theresia; Respati, Harianto; G. Sumarsono, Tanto (Efisiensi: Jurnal Penelitian dan Pengembangan Ilmu Manajemen, 2025)
Employees are essential assets in the operation of healthcare facilities and play a crucial role in a company's success. Kepanjen Eye Center (KECE) faces challenges in retaining high-quality employees amid intense competition. This study aims to analyze the influence of employer branding and compensation on employee retention, with job satisfaction as a mediating variable. This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 108 KECE employees and analyzed using path analysis. The results show that employer branding and compensation significantly influence job satisfaction. Job satisfaction also has a significant impact on employee retention and mediates the relationship between employer branding, compensation, and employee retention. In other words, strong employer branding and fair compensation enhance job satisfaction, ultimately leading to higher employee retention at KECE. In conclusion, effective employer branding strategies and a fair compensation system are crucial in creating a positive work environment and improving employee satisfaction and retention.